Discursive strategies in select mediatised social transformation advocacy in Nigeria. (April 2019) - Ademilokun, Mohammed Ayodeji
Abstract: This article discusses the discursive strategies used in negotiating the social transformation agenda in Nigeria. Data for the study comprise advocacy texts that touch on anti-corruption crusade, entrenchment of democratic values and security of lives and properties. The data were drawn from speeches and jingles circulated by institutional agencies on television and radio stations and covered the period July 2013 to July 2018. The five-year span was informed by the wide gamut of negative realities in the nation at the time frame which led to increased mediatisation of social transformation messages in the nation. Fairclough's (2015) dialectical relational approach constitutes the theoretical anchor for the study. Data analysis reveals that the discourse participants deploy framing, legitimation, rhetorical questions, linguistic nativism, metaphorisation of social transformation acts and accentuation of the repercussions of negative actions. The paper concludes that even though the discourse of social transformation in Nigeria is hinged on the desire to impact the society, it also reflects the power disequilibrium in the society which privileges the government and reflects in the construction of Nigeriás problems and its solutions as citizen-oriented.